The Developing a Pictured Story Book as Emotional Intelligence for Low Grade Elementary School Students - Hazrati, Rima; Fitri, Susi; Wirasti, RA. Murti Kusuma (Universitas Malikussaleh, 2020)
This study uses a type of research & development method or in English (Research and Development) terms. The development model in the study uses the Borg and Gall model, where this model comes from the results of thought, is still a concept that is empirically tested and its implementation organized from planning, implementation to evaluation of the results. The purpose of this study is to produce a product that is a picture story book about emotional intelligence that meets the criteria of feasibility aspects. Emotional intelligence should begin to be developed as early as possible because it can make children have high enthusiasm in learning or liked by their friends in the playground. The development of this illustrated storybook uses components or dimensions of emotional intelligence from Daniel Goleman. There are 5 dimensions that will be used for 5 themes in illustrated storybooks namely self-awareness, self-regulation, motivation, empathy, social skills. The form of the book that will be created with hard cover and will be dominated by images. The goal of developing this storybook media is aimed at lower primary school students, which are around the ages of 6 to 9 years.